Dermatophytosis: Prevalence of Dermatophytes and Non-Dermatophyte Fungi from Patients Attending Arsho Advanced Medical Laboratory, Addis Ababa, Ethiopia - Adane Bitew (Dermatology Research and Practice)
Background. Dermatophytosis is a disease of major public health problem around the globe causing a considerable morbidity. Objective. To study the prevalence of dermatophytosis and the spectrum of fungi implicated in causing the infection. Methods. Nail, skin, and scalp scrapings were collected from 318 patients and were used for microscopy and culture study. Fungal pathogens were identified by studying the macroscopic and microscopic characteristics of their colonies. Result. Tinea capitis was the predominant clinical manifestation consisting of 48.1% of the cases. Among 153 patients with tinea capitis, 73.2% were in the age group of 1-14 years. Of 318 study participants, 213 (67.98%) were found to be positive for dermatophytosis microbiologically. Out of 164 fungal isolates, 86 were dermatophytes and 78 were non-dermatophyte fungi. Among 86 dermatophytes, T. violaceum represented 38.4% of dermatophyte isolates and 89.7% of the isolates were recovered from tinea capitis. Of 76 non-dermatophyte molds, Aspergillus spp., Scytalidium dimidiatum, and Cladosporium spp. were the most common isolates, respectively. Conclusions. Failure to detect or isolate fungal pathogens in a large number of clinical samples revealed the limitation of clinical diagnosis in differentiating dermatophytosis from other skin infections demonstrating that clinical diagnosis should be coupled with laboratory methods. Recovery of large number of non-dermatophyte fungi along with dermatophytes in our study showed that non-dermatophyte fungi are emerging as important causes of dermatophytosis, warranting the implementation of intensive epidemiological studies of dermatophytosis across the country.